Trends in use of neonatal CPAP: a population-based study - Bowen Jennifer R; Algert Charles S; Badgery-Parker Tim; Roberts Christine L; Nassar Natasha (BMC, 2011)
Abstract Background Continuous positive airway pressure (CPAP) is used widely to provide respiratory support for neonates, and is often the first treatment choice in tertiary centres. Recent trials have demonstrated that CPAP reduces need for intubation and ventilation for infants born at 25-28 weeks gestation, and at > 32weeks, in non-tertiary hospitals, CPAP reduces need for transfer to NICU. The aim of this study was to examine recent population trends in the use of neonatal continuous positive airway pressure. Methods We undertook a population-based cohort study of all 696,816 liveborn neonates ≥24 weeks gestation in New South Wales (NSW) Australia, 2001-2008. Data were obtained from linked birth and hospitalizations records, including neonatal transfers. The primary outcome was CPAP without mechanical ventilation (via endotracheal intubation) between birth and discharge from the hospital system. Analyses were stratified by age ≤32 and > 32 weeks gestation. Results Neonates receiving any ventilatory support increased from 1,480 (17.9/1000) in 2001 to 2,486 (26.9/1000) in 2008, including 461 (5.6/1000) to 1,465 (15.8/1000) neonates who received CPAP alone. There was a concurrent decrease in mechanical ventilation use from 12.3 to 11.0/1000. The increase in CPAP use was greater among neonates > 32 weeks (from 3.2 to 11.8/1000) compared with neonates ≤32 weeks (from 18.1 to 32.7/1000). The proportion of CPAP > 32 weeks initiated in non-tertiary hospitals increased from 6% to 30%. Conclusions The use of neonatal CPAP is increasing, especially > 32 weeks gestation and among non-tertiary hospitals. Recommendations are required regarding which infants should be considered for CPAP, resources necessary for a unit to offer CPAP and monitoring of longer term outcomes.